Bibliographisch-thematische Studie über Bestimmungstabellen für landwirtschaftlich-gärtnerisch wichtige Dipterenlarven. - Köppen, Herbert (Contributions to Entomology = Beiträge zur Entomologie, 1972)
This paper covers the period from 1950 to 1969; six comprehensive keys to the larvae of the Diptera families of all suborders, a total of 102 separate keys to larvae of genera or species of nine Diptera families selected for their economic significance, and nine keys of the same kind but published before 1950 are listed in the bibliographic parts and discussed in the text; eight keys of the different categories are chosen as instructive examples and reproduced in their originals texts, in translations or adaptations. The evaluating parts for each family cover a total of 356 species of 98 genera.